2021
DOI: 10.1007/s11248-021-00275-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of myostatin deficiency with collagen related disease-umbilical hernia and tippy toe standing in pigs

Abstract: Herein, we investigate the high incidence of umbilical hernia and tippy-toe standing and their underlying changes in gene expression and proliferation in myostatin knockout (MSTN -/-) pigs. Thirtysix male MSTN -/pigs were generated by somatic cell nuclear transfer (SCNT). These pigs presented a considerably high incidence of tippy-toe standing and umbilical hernia (69.4% and 61.1%, respectively). The tendon to body weight ratio was significantly lower than wild-type pigs (0.202 ± 0.017 vs 0.250 ± 0.004, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In a study of MSTN knockout cattle, Smad2/3 bound to TET1 to regulate the DNA methylation modification to regulate the expression of myogenic factors to control muscle size [ 61 ], and it can also bind to the PDE5A promoter region to regulate glucose metabolism in the myocardium [ 25 ]. In Mstn −/− pigs, the reduction of Smad2/3 inhibited the atrophic effect of activin receptor-like kinase 5 (ALK5) [ 62 ]. Smad can bind to the promoter sequence of target genes and regulate gene transcription activity, thereby affecting gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of MSTN knockout cattle, Smad2/3 bound to TET1 to regulate the DNA methylation modification to regulate the expression of myogenic factors to control muscle size [ 61 ], and it can also bind to the PDE5A promoter region to regulate glucose metabolism in the myocardium [ 25 ]. In Mstn −/− pigs, the reduction of Smad2/3 inhibited the atrophic effect of activin receptor-like kinase 5 (ALK5) [ 62 ]. Smad can bind to the promoter sequence of target genes and regulate gene transcription activity, thereby affecting gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…One of these MSTN -edited models, its progeny, or its crosses were further investigated . These include investigations on fiber-type distribution and expression of myosin heavy chain isoforms; shift from slow- to fast-twitch muscle fibers in skeletal muscle; internal organ size; semen quality and fertilization ability; reproductive trait characterization in MSTN -edited crosses; collagen-related pathological features (umbilical hernia and tippy toe standing); regulation of body fat deposition; fibrinogen levels and fibrin clot structure; esophageal striated muscle development and regulation of muscle fiber types; extraocular muscles; cardiac extracellular matrix; growth of smooth muscle in uterine horns of MSTN mutant gilts; smooth muscle content in corpus cavernosum of MSTN mutant boars; erythrocyte osmotic fragility, hematological parameters, and fatty acid composition of serum and erythrocyte membranes; miR-455-3p regulation of myoblast differentiation; composition and alteration of gut microbiota; analysis of meat and fatty acids characteristics; and development of a restriction enzyme-mediated PCR-RFLP assay for genotyping MSTN mutant pigs …”
Section: Targeting the Mstn Gene In Pigsmentioning
confidence: 99%
“…Since Wang et al [ 45 ] suggested that commercial breeds would be more sensitive to the KO of endogenous genes, Zou et al [ 46 ] generated two healthy Duroc pigs with the Belgian Blue mutation only in heterozygosity, but they did not show double muscling at the neonatal stage. It could be explained by a recent finding that showed in commercial MSTN KO pigs, the decreased expression level of type I collagen and Scleraxis, could result in umbilical hernia and tippy-toe standing problems typified by the tendon and linea alba dysfunction [ 47 ].…”
Section: Application Of New Breeding Technology In Pig Productionmentioning
confidence: 99%